THE ASSOCIATION BETWEEN PERCEIVED AUDIT FIRM SERVICE QUALITY AND BEHAVIOURAL INTENTIONS - Morton, Anja; Scott, Don (The journal of contemporary issues in business and government, 2007)
The aim of this study was to develop and test an instrument for measuring service quality in an audit firm setting and then use this instrument to evaluate the influence of service quality perceptions on audit firm clients’ intentions to purchase additional services. Based on qualitative research and secondary data, a questionnaire-based instrument was developed and assessed for reliability and validity. Data collected with the developed instrument was then used in a canonical correlation analysis. The developed instrument was found to be reliable and valid. It was further found that enhanced service quality was not associated with the provision of additional services but was associated with recommendations to prospective new clients and was weakly associated with retention of the audit firm.